2001
DOI: 10.1108/eum0000000006118
|View full text |Cite
|
Sign up to set email alerts
|

“Blanket” approaches to promoting ICT in small firms: some lessons from the DTI ladder adoption model in the UK

Abstract: The current push for small firms to be “wired up to the digital marketplace” is evidenced by the number of initiatives targeting small and medium‐sized enterprises (SMEs) to promote this activity. Like other governments worldwide, UK Online’s SME targets (together with the supporting DTI adoption ladder) exemplify the “conventional wisdom” view of a homogeneous small business sector, within which firms take an ordered, sequential progression on the route to Internet technology adoption. This approach is questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 30 publications
4
191
0
1
Order By: Relevance
“…The way Government initiative targets are set and defined point towards a 'generalist' view of SMEs (Martin & Matlay, 2001). In work done by MacGregor and Vrazalic (2005) eBusiness was recognised as a major source of competitive advantage and they state that this now means that Governments worldwide have recognised this and are creating funding schemes and initiatives to facilitate e-Commerce adoption in small businesses.…”
Section: Government Intervention In the Adoption Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The way Government initiative targets are set and defined point towards a 'generalist' view of SMEs (Martin & Matlay, 2001). In work done by MacGregor and Vrazalic (2005) eBusiness was recognised as a major source of competitive advantage and they state that this now means that Governments worldwide have recognised this and are creating funding schemes and initiatives to facilitate e-Commerce adoption in small businesses.…”
Section: Government Intervention In the Adoption Processmentioning
confidence: 99%
“…The Department for Trade and Industry (DTI) a United Kingdom (UK) central government department who recently changed its' name to the Department for Business, Enterprise and Regulatory Reform (BERR) published the governments 'adoption ladder' for their UK online initiative. The model underpins much of the understanding around the area of ICT adoption in SMEs (Sergeant 2000 cited in Martin and Matlay, 2001). Unfortunately, the only flexibility built into the model is to imply that not all businesses will start at stage one.…”
Section: Government Intervention In the Adoption Processmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on one highly relevant determinant of the system of innovation for the diffusion of IS in SMEs, namely government programs (e.g., Berkeley et al 1996;Cuadrado and Garcia 2004;Gengatharen et al 2005;Lebre 1995;Simpson and Docherty 2004). Importantly, there is a general concern regarding the quality of the government support to SME innovation (Johnson 2005;Martin and Matlay 2001;Mole 2002;Nugent and Yhee 2002). The topic is even more relevant if we consider that our empirical work demonstrated that there is a negative and enduring context affecting programs.…”
Section: Introductionmentioning
confidence: 99%